Reflections of the Everyday. Exploring the essence of Ecuadorian cinema through Ratas, Ratones, Rateros - Idrovo, René (Nawi, 2024)
This essay analyzes the film Ratas, Ratones, Rateros (1999), by Ecuadorian director Sebastián Cordero, as a reflection of the social problems that affect contemporary Ecuador. Through a textual analysis of the work, it is examined how the main characters, two cousins ​​who are dedicated to theft and crime, represent the Creole liveliness, social resentment and corruption that are some of the characteristic features of Ecuadorian society. Likewise, the film is contextualized with the political and economic scenario of the country at the end of the nineties, marked by the banking crisis, dollarization and government instability. The conclusion to be reached is that Ecuadorian cinema, more than a nationalist art, functions as a mirror of daily reality; as a reflection of the identity and social problems of Ecuadorians.
Keywords: Sebastián Cordero; cinema; Ecuador; social problems; national identity